A new species of the Drosophila tripunctata group (Diptera: Drosophilidae) associated with fallen flowers of six Lecythidaceae species in the Amazon Rainforest - Maciel, Vinícius Queiroz; Burlamaqui, Tibério Cesar Tortola; Santa-Brígida, Rosângela; Santos, Rita De Cássia Oliveira; Martins, Marlúcia Bonifácio (Zootaxa, 2023)
The tripunctata group falls under the subgenus Drosophila Fallén, 1823 of the genus Drosophila Fallén, 1823, and is composed of four subgroups and 17 species not assigned to subgroups. This group is widely distributed throughout tropical regions and is predominantly found in preserved forest environments. With a predicted high number of cryptic species, the occurrence of intraspecific morphological polymorphisms made it difficult to establish lines in the laboratory. The capture of males for comparison of the terminalia makes it hard to identify and delimit species; however, these difficulties can be overcome through the use of techniques such as searching for species in naturally occurring places, establishing isofemale lines in the laboratory, or using molecular techniques. In this work, we search for imagoes of species of the tripunctata group over present fallen flowers of the Lecythidaceae on the ground of the Amazon rainforest. The collected individuals were morphologically and molecularly analyzed. This species is described here under the binomial Drosophila lecythus sp. nov.